'All they do is drink coffee:' notes on café culture in Prishtina, Kosova. (2nd January 2022) - Canolli, Arsim
ABSTRACT: Drawing on evidence from participant observation and semi-structured interviews undertaken in the period 2011–2014, this paper explores the social life of café culture in Prishtina, Kosova. It focuses on everyday coffee drinking practices as an embodiment of civility, morality and identity, and provides a view of what constitutes café culture and how social identities are formed and shaped within/around/outside/in relation to cafés. It also highlights how values, norms, and identities are contested, negotiated and also reproduced in regular café-going in Prishtina. The focus shifts to spaces, routines, practices, ordinary events, as well as the constant discussion of café culture. Finally, it discusses how cafés have become social settings where the established codes of hospitality with their inherent demand for reciprocal conviviality are at play.